Model of Kiai Leadership Based on Local Wisdom: Preventing Radicalism and Building Education in the Global South - Muhammad Anas Ma`arif; Muhamad Arif; Mauhibur Rokhman; Ali Usman Hali; Ari Kartiko; Akhmad Sirojuddin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The role of the Kyai in maintaining the stability and character of santri (Islamic boarding school students) is a fundamental responsibility that cannot be replaced. The dynamic interplay of cultural diversity and varying social conditions must be carefully considered in managing pesantren, especially amidst the widespread issue of radicalism. This study aims to analyze how the Kyai's leadership model, grounded in local wisdom, functions as a strategy to prevent radicalism within pesantren environments, and how this model can contribute to the development of relevant and high-quality education in the Global South. It also explores the challenges faced by Kyai leadership when rooted in local cultural values. This research employs a qualitative method with a case study approach. The primary sources of data include Kyai, pesantren administrators, and santri, collected through observation, interviews, and documentation. The data analysis follows Yin's case study framework, involving pattern matching, explanation building, time-series analysis, and repeated observation. Data validity is ensured through triangulation of methods, sources, and theoretical perspectives. The findings reveal that the Kyai’s leadership model based on the prophetic (Nubuwwah) approach, integrated with the pesantren’s local wisdom namely the Panca Jiwa (five foundational values) and the four spiritual pillars serves as a key ideological defense mechanism against the spread of radicalism in the pesantren. Future research is recommended to expand this model across various pesantren and to apply methodological innovations that test the effectiveness of this integrated prophetic-local leadership approach in responding to global challenges.